hpmA Gene as a Detection Method of Proteus mirabilis Bacteria using real-time Polymerase Chain Reaction - Nurjayadi, Muktiningsih; Putri, Gladys Indira; Fitriyanti, Anisa; Declan, Jefferson Lynford; Novitasari; Abomoelak, Bassam (Jurnal Kesehatan Masyarakat, 2025)
Proteus mirabilis is pathogenic bacteria that can cause gastrointestinal infections, bacteremia, and Urinary Tract Infections (UTI). Therefore, it is necessary to have a fast, sensitive, specific, and accurate detection method to identify Proteus mirabilis. This study aims to determine the confirmation, specificity, and sensitivity test of the hpmA gene primer to detect Proteus mirabilis quick and precise using the real-time Polymerase Chain Reaction method. Gradient Polymerase Chain Reaction results showed the hpmA primer has an amplicons length of 195 bp and the optimum annealing temperature at 60°C. The primer pair produced Ct value of 10.40±0.18 and showed one peak in the melting curve with Tm value of 81.84°C±0.02 by real-time PCR. Furthermore, the hpmA primer was also able to distinguish target and non-target bacteria based on the difference in Ct and Tm value formed. Based on these results, the concentration of bacterial DNA that can be detected by primers reached 3.2 pg/μL, equivalent to the concentration of target bacteria that can be detected by primers is 10.24×102 CFU. In the next step, hmpA primer will be developed to detect Proteus mirabilis in artificial contaminated samples using real-time PCR.